Structural and functional attributes of Heuweltjies in the fynbos and succulent Karoo biomes: the interaction of termites, vegetation and geochemistry - Vermonti, Nicola (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScConsEcol)--Stellenbosch University, 2022.